Antibiotic-associated diarrhea: state-of-the-art - D. V. Piliev; S. I. Achkasov; T. K. Korneva; O. I. Sushkov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2014)
The aim of review. To analyse modern concepts on antibiotic-associated diarrhea, to determine its place in the pattern of total morbidity.Key points. Wide antibiotic application in all sections of medicine along with beneficial action has series of essential side effects, including antibiotic-associated diarrhea. Its extreme and most severe manifestation is pseudomembranous colitis, caused by toxin-producing Clostridium difficile strains. This etiological agent in modern world has got significant association with hospitals and assisted-care facilities, therefore it can spread in out-patient conditions as well at the present time. Mutations resulting in antibiotic resistance, increasing toxin production or promoting sporulation, considerably increase virulence and prevalence of these opportunistic microorganisms.Conclusion. The further studies on development of effective prophylactic and treatment methods of antibiotic-associated diarrhea are required, especially for most severe complication — pseudomembranous colitis. It is necessary to limit application of antibiotics, develop strict indications to their application.